2015
DOI: 10.3892/mmr.2015.4514
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal epigenetic regulation of the gene expression levels of Wnt2b and Wnt7b: Implications for neural tube defects

Abstract: The association between Wnt genes and neural tube defects (NTDs) is recognized, however, it remains to be fully elucidated. Our previous study demonstrated that epigenetic mechanisms are affected in human NTDs. Therefore, the present study aimed to evaluate whether Wnt2b and Wnt7b are susceptible to abnormal epigenetic modification in NTDs, using chromatin immunoprecipitation assays to evaluate histone enrichments and the MassARRAY platform to detect the methylation levels of target regions within Wnt genes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Results from recent studies show that not only gene mutations but also aberrant gene expression are important in NTDs [27]. Previous work from our laboratory has confirmed that abnormal expression of Wnt2b and Wnt7b is involved in human NTDs [28]. In this study, we attempted to explore the role of abnormal expression of HOX genes in NTDs as well as its underlining regulatory mechanism, based our data from transcriptome profile analysis of RA-induced mouse NTDs embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Results from recent studies show that not only gene mutations but also aberrant gene expression are important in NTDs [27]. Previous work from our laboratory has confirmed that abnormal expression of Wnt2b and Wnt7b is involved in human NTDs [28]. In this study, we attempted to explore the role of abnormal expression of HOX genes in NTDs as well as its underlining regulatory mechanism, based our data from transcriptome profile analysis of RA-induced mouse NTDs embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Both genetic and epigenetic factors have been studied to identify the etiology of NTDs, especially since folate deficiency has been indicated as a cofactor of NTD occurrence [34]. Recent studies suggested that histone modifications such as acetylation or methylation correlated with the occurrence of NTD in mouse or chick embryos [35][36][37][38][39]. Further, chromatin modifications have been linked to defective neurogenesis and patterning of the embryonic spinal cord [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…WNT3a deficiency causes irrevocable damage to the hematopoietic stem cell's self renewal, resulting in defects in progenitor cell differentiation [12]. WNT7b can act both canonically and non-canonically by involving in convergent extension movement and increase in signaling, thus possibly leading to distorted neural development [13]. Proteinprotein interactions (PPIs) are important for cell-cell communication, signaling pathways and several other biological processes and main goal behind these PPIs is to find out specific function of specific protein [14].…”
Section: Introductionmentioning
confidence: 99%